The Chemical Composition and Biological Activities of Essential Oils from Zanthoxylum rhetsa Grown in Son La, Northwest Vietnam. (12th July 2021) - Pham, Cao Bach; Cam, Thi Inh; Tran Thi, Tuyen; Quan, Pham Minh; Toan, Tran Quoc; Do, Huu Nghi; Thu Thuy, Dinh Thi; Nguyen, Thi Thuy; Trinh, Anh Vien; Pham, Thi Hong Minh; Pham, Quoc Long; Hien, Tran Thien; et al.
Abstract : Essential oils (EOs) from the stem barks, leaf petioles, fruit petioles, fresh leaves, and fresh and dried fruits of Zanthoxylum rhetsa were extracted by hydrodistillation. The volatile compounds of the products were analyzed by gas chromatography (GC-FID) and gas chromatography/mass spectrometry (GC/MSD). Monoterpene hydrocarbons formed the predominant fraction of all six EO samples, of which sabinene is one of the major components (from 12.37% to 41.13%). For the leaf petiole EO, limonene (25.01%), sabinene (14.56%), and linalool (12.63%) are the major constituents, while the main constituents of fruit petiole EO were terpinolene (19.66%), terpinen-4-ol (19.07%), and sabinene (17.83%). The major components of stem bark EO are terpinen-4-ol (18.23%), sabinene (12.37%), α -phellandrene (7.34%), β -phellandrene (6.32%), and γ -terpinene (6.12%), while sabinene (38.35%), terpinen-4-ol (13.71%), γ -terpinene (6.47%), and limonene (6.02%) are the major constituents of fresh leaf EO. For the EOs of dried fruits and fresh fruits, sabinene, terpinolene, limonene, and terpinen-4-ol are the major constituents. The essential oils were also tested for their cytotoxic and antimicrobial activities. The results revealed that six EOs at concentrations of 50 μ g/mL exhibited inhibitory activity against at least one tested cancer cell line but were nontoxic on Vero normal cells. Most EOs showed moderate antimicrobial activity against F. oxysporum ; however, there were no obvious activity against B. subtilis and S. aureus .